Intrinsic structure of pentapeptide Leu-enkephalin: geometry optimization and validation by comparison of VSCF-PT2 calculations with cold ion spectroscopy. Issue 38 (20th September 2018) - Roy, Tapta Kanchan; Kopysov, Vladimir; Pereverzev, Aleksandr; Šebek, Jiří; Gerber, R. Benny; Boyarkin, Oleg V.
Abstract : Intrinsic structure of pentapeptide Leu-enkephalin: quantum VSCF calculations meet cold ion spectroscopy. Abstract : The intrinsic structure of an opioid peptide [Ala 2, Leu 5 ]-leucine enkephalin (ALE) has been investigated using first-principles based vibrational self-consistent field (VSCF) theory and cold ion spectroscopy. IR-UV double resonance spectroscopy revealed the presence of only one highly abundant conformer of the singly protonated ALE, isolated and cryogenically cooled in the gas phase. High-level quantum mechanical calculations of electronic structures in conjunction with a systematic conformational search allowed for finding a few low-energy candidate structures. In order to identify the observed structure, we computed vibrational spectra of the candidate structures and employed the theory at the semi-empirically scaled harmonic level and at the first-principles based anharmonic VSCF levels. The best match between the calculated "anharmonic" and the measured spectra appeared, indeed, for the most stable candidate. An average of two spectra calculated with different quantum mechanical potentials is proposed for the best match with experiment. The match thus validates the calculated intrinsic structure of ALE and demonstrates the predictive power of first-principles theory for solving structures of such large molecules.